Evidence for Multiple Binding Modes in the Initial Contact Between SARS‐CoV‐2 Spike S1 Protein and Cell Surface Glycans. Issue 1 (7th November 2022) - Parafioriti, Michela; Ni, Minghong; Petitou, Maurice; Mycroft‐West, Courtney J.; Rudd, Timothy R.; Gandhi, Neha S.; Ferro, Vito; Turnbull, Jeremy E.; Lima, Marcelo A.; Skidmore, Mark A.; Fernig, David G.; Yates, Edwin A.; et al.
Abstract: Infection of host cells by SARS‐CoV‐2 begins with recognition by the virus S (spike) protein of cell surface heparan sulfate (HS), tethering the virus to the extracellular matrix environment, and causing the subunit S1‐RBD to undergo a conformational change into the 'open' conformation. These two events promote the binding of S1‐RBD to the angiotensin converting enzyme 2 (ACE2) receptor, a preliminary step toward viral‐cell membrane fusion. Combining ligand‐based NMR spectroscopy with molecular dynamics, oligosaccharide analogues were used to explore the interactions between S1‐RBD of SARS CoV‐2 and HS, revealing several low‐specificity binding modes and previously unidentified potential sites for the binding of extended HS polysaccharide chains. The evidence for multiple binding modes also suggest that highly specific inhibitors will not be optimal against protein S but, rather, diverse HS‐based structures, characterized by high affinity and including multi‐valent compounds, may be required. Abstract : More than one way to get in : A hexasaccharide bound to site I of the spike protein in two binding modes (orange and green tubes) shows that multiple binding modes between heparan sulfate (HS) and S1 (electrostatic potential map on the surface) are allowed. The hypothetical macromolecular complex HS−S1 does not interfere with the interaction involving S1‐RBD and ACE2, thus supporting the co‐receptor role of HS in the activation of the SARS‐CoV‐2 S protein.